Perbandingan Hasil Pendapatan Usahatani Padi antar Kecamatan di Kabupaten Langkat - Sitompul, Ahmad Fajrin; Afifuddin, Sya'ad; Khardinata, E. Harso; Siregar, Tumpal H.S. (AGRISAINS: Jurnal Ilmiah Magister Agribisnis, 2020)
The main target of agricultural development is to increase agricultural production and income of rice farmers, therefore the activities of the agricultural sector are endeavored to run smoothly by increasing food products through intensification, extensification and diversification of agriculture which is expected to improve the standard of living of farmers, expand employment opportunities for the community still depends on the agricultural sector. The level of income of farmers in general is affected by several components, namely: the amount of production, selling prices, and costs incurred by farmers in their agriculture. To find out how much the cost, revenue, income, R / C Ratio, the difference in rice farm income between the Districts in Langkat District. The data used are primary data sourced from the groups of three rice farmers in Secanggang District, Sei Bingei District, and Batang Serangan District. Each sub-district was taken as many as sixteen farmer groups by giving a questionnaire list. The research model is a quantitative model using F-test techniques using SPSS version 16.0.Â  The results showed that there were differences in costs, revenues, income, and R / C Ratio of lowland rice farming in Secanggang District, Sei Bingei District, and Batang Serangan District in Langkat Regency.